Aberration‐free aspherical lens shape for shortening the focal distance of an already convergent beam. (6th October 2017) - Sutter, John P.; Alianelli, Lucia
Abstract : The ideal lens surface for refocusing an already convergent beam is found to be one sheet of a Cartesian oval. This result is applied to the optimal construction of a compound refractive lens for X‐ray nanofocusing. Abstract : The shapes of single lens surfaces capable of focusing divergent and collimated beams without aberration have already been calculated. However, nanofocusing compound refractive lenses (CRLs) require many consecutive lens surfaces. Here a theoretical example of an X‐ray nanofocusing CRL with 48 consecutive surfaces is studied. The surfaces on the downstream end of this CRL accept X‐rays that are already converging toward a focus, and refract them toward a new focal point that is closer to the surface. This case, so far missing from the literature, is treated here. The ideal surface for aberration‐free focusing of a convergent incident beam is found by analytical computation and by ray tracing to be one sheet of a Cartesian oval. An `X‐ray approximation' of the Cartesian oval is worked out for the case of small change in index of refraction across the lens surface. The paraxial approximation of this surface is described. These results will assist the development of large‐aperture CRLs for nanofocusing.